Development and Validation of UV-Visible Spectrophotometric Baseline Manipulation Method for Simultaneous Quantitation of Tenofovir Disoproxil Fumarate and Emtricitabine in Pharmaceutical Dosage Form - Vishnu P. Choudhari; Sanket R. Parekar; Subhash G. Chate; Pradeep D. Bharande; Rajiv R. Singh; Bhanudas S. Kuchekar (Journal of Spectroscopy)
A simple, economical, precise, and accurate new UV-visible spectrophotometric baseline manipulation method for simultaneous determination of tenofovir disoproxil fumarate (TE) and emtricitabine (EM) in combined tablet dosage form has been developed. The method is based on baseline manipulation (difference) spectroscopy where amplitudes at 261 and 289.9 nm were selected to determine TE and EM, respectively, in combined formulation, and distilled water was used as solvent. Both drugs obey Beer’s law in the concentration ranges of 4–20 μg/mL for TE and 6–30 μg/mL for EM. The results of analysis have been validated statistically, and recovery studies confirmed the accuracy of the proposed method which was carried out by following the ICH guidelines.